Synthèse Générale des entretiens réalisés à Ouaga - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2022)
This text presents the general synthesis of data collected in Ouagadougou as part of the research project: Institutions judiciaires pénales et trajectoires sociales des adolescents/jeunes au Burkina Faso: formes et modèles de punitions endogènes/locales. The actors who took part in these interviews were: the examining magistrate, the juvenile judge, the BRPE commissioner and representatives of the customary authorities. These interviews focused on the types and procedures of management, types of punishment and their relationship with gender and social class. Community mediation mechanisms and the population's perception of the different types of punishment and judicial bodies (modern and traditional).
Keywords: Administration of Justice; Teenagers; Youth; Punishment